2005
DOI: 10.1063/1.1851016
|View full text |Cite
|
Sign up to set email alerts
|

Buried stressors in nitride semiconductors: Influence on electronic properties

Abstract: An analysis is presented on the effect of the strain field originating from a subsurface stressor ͑point source of dilatation or a dilatating ellipsoidal inclusion͒ on the electronic properties of nitride semiconductors. With good accuracy, real quantum dots can be modeled as such stressors. We consider the following material structure design: a uniform semi-infinite GaN matrix with a buried stressor or a GaN matrix with a single ͑In,Ga͒N quantum well, which is grown pseuodomorphically between the stressor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 54 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Although numerical simulations provide a complete solution to the problem, analytical calculations still play an important role. In a number of studies it has been confirmed that descriptions of quantum dots using idealized analytical models and more rigorous numerical techniques are in good agreement (Daruka et al, 1999;Andreev et al, 1999;Romanov et al, 2001Romanov et al, , 2005Jonsdottir et al, 2006). Exact analytical formulas can significantly facilitate analysis of material properties.…”
Section: Introductionmentioning
confidence: 64%
“…Although numerical simulations provide a complete solution to the problem, analytical calculations still play an important role. In a number of studies it has been confirmed that descriptions of quantum dots using idealized analytical models and more rigorous numerical techniques are in good agreement (Daruka et al, 1999;Andreev et al, 1999;Romanov et al, 2001Romanov et al, , 2005Jonsdottir et al, 2006). Exact analytical formulas can significantly facilitate analysis of material properties.…”
Section: Introductionmentioning
confidence: 64%
“…The obtained results demonstrate that when an inclusion is placed in an elastic half-space, hydrostatic stress occurs and depends on the relative position between the cylinder and the free surface. This affects the mechanical and physical properties of the material, which has been proven by many studies [8].…”
Section: Discussionmentioning
confidence: 95%
“…The correctness of the found elastic fields of cylinder in the elastic half-space given by Eqs. (8)(9)(10)(11)(12)(13) is checked by comparing to the case of infinite space, where the hydrostatic stress on the outside of the cylinder is zero [13]. There is hydrostatic stress in the elastic half-space Eqs (14), similar to the elastic field of ITDD in the half-space [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations